2016
DOI: 10.1124/mol.116.106252
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Phosphatidylinositol 3-Kinase Is Essential for Canonical GPCR Signaling

Abstract: G protein-coupled receptors (GPCRs), the largest family of signaling receptors, are critically regulated by endosomal trafficking, suggesting that endosomes might provide new strategies for manipulating GPCR signaling. Here we test this hypothesis by focusing on class III phosphatidylinositol 3-kinase (Vps34), which is an essential regulator of endosomal trafficking. We verify that Vps34 is required for recycling of the β2-adrenoceptor (β2AR), a prototypical GPCR, and then investigate the effects of Vps34 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…We verified that the rapamycin-induced localization of 3-phosphatase or 4-phosphatase to early endosomes results in reduced endosomal PtdIns(3,4)P 2 but that of 5-phosphatase dose not ( Figure 5 E,F). The activity of FKBP-MTM1, FKBP-INPP4B, and FKBP–Inp54p has been well demonstrated in previous works [ 60 , 62 , 63 , 64 , 65 ]. We investigated if rapamycin treatment (40 nM, 5 min incubation) for lipid phosphatase targeting may indirectly affect AKT activation in our experiments, as it was shown that rapamycin inhibits mTORC1 activity acutely [ 66 ] and mTORC2 activity chronically [ 67 ].…”
Section: Resultssupporting
confidence: 66%
“…We verified that the rapamycin-induced localization of 3-phosphatase or 4-phosphatase to early endosomes results in reduced endosomal PtdIns(3,4)P 2 but that of 5-phosphatase dose not ( Figure 5 E,F). The activity of FKBP-MTM1, FKBP-INPP4B, and FKBP–Inp54p has been well demonstrated in previous works [ 60 , 62 , 63 , 64 , 65 ]. We investigated if rapamycin treatment (40 nM, 5 min incubation) for lipid phosphatase targeting may indirectly affect AKT activation in our experiments, as it was shown that rapamycin inhibits mTORC1 activity acutely [ 66 ] and mTORC2 activity chronically [ 67 ].…”
Section: Resultssupporting
confidence: 66%
“…This GPCR responds physiologically to changes in extracellular catecholamine concentration that span a wide range of time scales, through sequential bouts of Gs-coupled stimulation of cAMP production from the plasma membrane and then endosomes after agonist-induced receptor internalization 14 . Unlike polypeptide hormone receptors which are stably sequestered after endocytosis, β2ARs recycle efficiently and cycle continuously in the prolonged presence of agonist 15 , thus activating Gs transiently from each location during iterative trafficking cycles 16 . Endosomal activation has only a small effect on global cAMP elevation but is essential for efficient downstream signaling to cAMP-dependent gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly as in the EGFR sensing systems, the activity dynamics of these receptors is also tightly regulated by the endosomal trafficking. Even more, this regulation is mediated via PI3K, an Akt activator (Uchida et al , ). Thus, given that conditions for critical organization and maintenance in the vicinity of a SN bifurcation are also possible, it is likely that similar mechanism can confer responsiveness of GPCRs to time‐varying growth factor signals.…”
Section: Discussionmentioning
confidence: 99%